2023
DOI: 10.3390/s23031119
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Machine-Learning-Assisted Robust Magnetometer Based on Randomly Oriented NV-Ensembles in Diamond

Abstract: Quantum magnetometry based on optically detected magnetic resonance (ODMR) of nitrogen vacancy centers in nano- or micro-diamonds is a promising technology for precise magnetic-field sensors. Here, we propose a new, low-cost and stand-alone sensor setup that employs machine learning on an embedded device, so-called edge machine learning. We train an artificial neural network with data acquired from a continuous-wave ODMR setup and subsequently use this pre-trained network on the sensor device to deduce the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…If the crystal orientation is known, the parallel B 0 -field component can be determined by splitting the resonances and the angle of incidence can be calculated back. Homrighausen et al [29] have already demonstrated this in a fiber-based setup. The Hahn echo, in which the NV center becomes sensitive to alternating magnetic fields whose frequency corresponds to twice the pulse spacing τ, is suitable for measuring AC fields.…”
Section: Discussionmentioning
confidence: 88%
“…If the crystal orientation is known, the parallel B 0 -field component can be determined by splitting the resonances and the angle of incidence can be calculated back. Homrighausen et al [29] have already demonstrated this in a fiber-based setup. The Hahn echo, in which the NV center becomes sensitive to alternating magnetic fields whose frequency corresponds to twice the pulse spacing τ, is suitable for measuring AC fields.…”
Section: Discussionmentioning
confidence: 88%
“…The efficiency of the required calculation is such that trained NNs can be converted into compact and efficient TensorFlow Lite models, with a size of approximately 90 kB. These models are suitable for deployment and execution on microcontrollers, which would minimize resource demands and enable data collection and estimation on the same device, leading to a significant reduction in latency [49,50]. We can expect that, during data collection of photon-counting measurements, different chunks of measured time-delays are fed into the trained NN models for inference in real time.…”
Section: Computation Efficiencymentioning
confidence: 99%
“…Generally, the Bayesian parameter estimation method will be computationally time-consuming, even in simple systems. This hampers the prospects for real-time estimation and for the integration of the inference process in the actual measurement device taking the data, which would be desirable for reduced latency and energy consumption [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…To read out fluorescence signals, a customized transimpedance amplifier (TIA) is used described in a previous publication [37]. The TIA output voltage is fed into a lock-in amplifier (LIA) (MFLI, Zurich Instruments, Zurich, Switzerland).…”
Section: Measurement Setupmentioning
confidence: 99%